NILAI-NILAI MALAQBIQ DI KALANGAN REMAJA (STUDI TENTANG PELESTARIAN NILAI-NILAI MALAQBIQ DI POLEWALI MANDAR) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
Indonesia is one of the countries in the world that has more than 300 tribes spreading from Sabang to Marauke. All the tribes in it making Indonesia have a diverse local culture or traditional cultures. The development of the local culture in each region shows the level of community concern for their tribe’s culture. And in the development of traditional culture in a country, everybody expected that the young generation should also give their contribution. In social life, the culture will never be separated from one's personal self, especially for the young generation who still have an imbalance level of mindset and actions, so for that, it takes a long learning process to better understand the behaviour, mindset, and also the idea of actions carried out by humans. The purpose of this study was to determine the existence of the habit malaqbiq in Polewali Mandar Regency. Knowing the preservation of malaqbiq values among the young generation of Polewali Mandar Regency.